2020
DOI: 10.1002/anie.201910555
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Labeling of Peptidoglycan with NIR‐II Dye Enables In Vivo Imaging of Gut Microbiota

Abstract: Deepening our understanding of mammalian gut microbiota has been greatly hampered by the lack of a facile, real‐time, and in vivo bacterial imaging method. To address this unmet need in microbial visualization, we herein report the development of a second near‐infrared (NIR‐II)‐based method for in vivo imaging of gut bacteria. Using d‐propargylglycine in gavage and then click reaction with an azide‐containing NIR‐II dye, gut microbiota of a donor mouse was strongly labeled with NIR‐II fluorescence on their pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 43 publications
0
60
0
Order By: Relevance
“…), where the quantity of bacteria is relatively low and the distributions are often random and irregular [2a, 10] . We recently reported a near infrared II (NIR‐II)‐based macrographic imaging method to visualize the distribution of gut microbiota in vivo [11] . However, owing to the diffraction limit of NIR‐II fluorescence, [12] this method cannot provide satisfactory spatial resolutions to precisely localize bacteria tissue‐wide.…”
Section: Introductionmentioning
confidence: 99%
“…), where the quantity of bacteria is relatively low and the distributions are often random and irregular [2a, 10] . We recently reported a near infrared II (NIR‐II)‐based macrographic imaging method to visualize the distribution of gut microbiota in vivo [11] . However, owing to the diffraction limit of NIR‐II fluorescence, [12] this method cannot provide satisfactory spatial resolutions to precisely localize bacteria tissue‐wide.…”
Section: Introductionmentioning
confidence: 99%
“…Significant labeling was observed with millimolar concentrations of d ‐amino acids (Figure 2B); this is comparable with previous publications, in which a concentration of 0.1–10 m m was often used. [ 24–28 ] The fluorescence intensity versus incubation time plateaued at 30 min, which is close to the doubling time (generation time) of S. aureus (Figure S1, Supporting Information). It was also found that 10 min sufficed to complete the reaction when 20 μ m of Cy5‐Tz was used (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 58%
“…[ 21–23 ] Imaging bacteria with d ‐amino acids in complex biological environment has demonstrated excellent bacteria targeting performance. [ 24–28 ]…”
Section: Introductionmentioning
confidence: 99%
“…recognition and transduction is more utilized due to its high flexibility in designing and engineering for different application scenarios. [306,307]. Until now, the fluorescent reporting strategies still play major roles in nucleic acidbased bioanalysis, especially in the biological and biomedical applications.…”
Section: Signal Recognition and Transduction Strategiesmentioning
confidence: 99%